Capacity, Collaboration, Credentials: Challenges to Psychology in the Caribbean - Dudley-Grant, Rita (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2014)
Psychologists in the Caribbean face significant challenges. Needs include high quality psychological services, educating more psychologists and expanding the profession to meet mental health difficulties within Caribbean Communities. Other subspecialties such as social psychology and organizational psychology are needed to promote change within the society still bearing the impact of slavery and colonialization. The challenges include “Brain drain” with talented youth migrating for educational and professional opportunities and with a few exceptions, a lack of local universities offering advanced degrees in psychology the field. Challenges also arise from a lack of self-definition of psychology in the Caribbean. These factors, academic, professional and institutional along with recommendations for action will be offered. The action plan of the Caribbean Regional Conference of Psychology, CRCP 2011 is incorporated. Psicólogos en el Caribe enfrentan desafíos importantes. Necesita incluir servicios psicológicos de alta calidad, educar a más psicólogos y expandir la profesión para resolver dificultades de salud mental en las comunidades del Caribe. Otras subespecialidades como la psicología social y Psicología Organizacional son necesarios para promover el cambio dentro de la sociedad sigue teniendo el impacto de la esclavitud y la colonización. Los desafíos incluyen «Brain drain» con jóvenes talentosos migrar para oportunidades educativas y profesionales y con unas pocas excepciones, la falta de universidades locales ofrecen títulos avanzados en el campo de Psicología. También surgen desafíos de una falta de autodefinición de Psicología en el Caribe. Se ofrecerán estos factores, académicos, profesionales e institucionales junto con recomendaciones para la acción. Se incorpora el plan de acción de la Conferencia Regional Caribe de Psicología, CRCP 2011.